2017
DOI: 10.1016/j.tet.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly functionalized 2-(pyrrolidin-1-yl)thiazole frameworks with interesting antibacterial and antimycobacterial activity

Abstract: A versatile, facile and concise approach to access to highly substituted functionalized 2-(pyrrolidin-1-yl)thiazole ring system is accomplished. The efficient protocol proceeds by the reaction of corresponding racemic or enantiomerically enriched pyrrolidines and readily available benzoylisothiocyanate in acetonitrile followed by sequential reaction of readily available alpha-bromo ketones in acetone. The selectivity and good yield in the desired product is another important advantage of this reaction protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We have previously reported the synthesis and some biological evaluation of pyrrolidine, aroylaminocarbo-N-thioylpyrrolidine [7,25], their several metal complexes [7], thiohydantoin [26] and pyrrolidine thiazole derivatives [27]. As a continuation of our work, and according to our experience, in this article we have prepared some new selected tetrahydropyrrolo [3,4- showed activity against the tested bacteria with a range of 0.9-125 μg/ cm 3 .…”
mentioning
confidence: 87%
“…We have previously reported the synthesis and some biological evaluation of pyrrolidine, aroylaminocarbo-N-thioylpyrrolidine [7,25], their several metal complexes [7], thiohydantoin [26] and pyrrolidine thiazole derivatives [27]. As a continuation of our work, and according to our experience, in this article we have prepared some new selected tetrahydropyrrolo [3,4- showed activity against the tested bacteria with a range of 0.9-125 μg/ cm 3 .…”
mentioning
confidence: 87%
“…After cooling, it was added to water and neutralized with NaHCO 3 solution. The products were crystallized from ethanol (Belveren et al, 2017;Ried, 1976;Sabbaghan, Alidoust, & Hossaini, 2011) (Figure 3).…”
Section: General Synthesis Of Substituted Phenylthiazoles (Final Comentioning
confidence: 99%
“…To increase binding sites with key proteins, the 3-(pyrimidin-4-yl)-4-(quinoxalin-6-yl)pyrazoles 22a, 22b, 22d was synthesized as shown in Scheme 3. Pyrimidine-4-carbaldehyde (17) [28] was synthesized from commercially available 1,1-dimethoxyacetone and N,N-dimethylformamide diemthyl acetal via 3 steps. Compound 20 was synthesized from compound 17 via 3 steps in the same reaction condition as described in Scheme 1.…”
Section: Synthesismentioning
confidence: 99%
“…Although including a thioamide linkage between the phenyl and pyrazole ring distinctly increased ALK5 inhibitory activity, as previously shown [16], the thioamide linkage was rather unstable and was slowly cleaved, to release a pyrazole ring, during long-term storage. of 20 It was reported that compounds containing a thiazole and pyrimidine moiety have useful biological activities, such as antibacterial [17], anticancer [18,19], antiviral [20], anti-inflammatory [21], and antimalarial properties [22].…”
Section: Introductionmentioning
confidence: 99%